A Review of Digital Health Strategies in 10 Countries With Young Populations: Do They Serve the Health and Wellbeing of Children and Youth in a Digital Age? - Holly, Louise; Smith, Robert Dean; Ndili, Njide; Franz, Christian; Stevens, Enow Awah Georges (Frontiers in Digital Health, 2022)
Children and youth merit special attention from digital health policymakers and practitioners because of the great potential for digital transformations to both enhance and undermine their health and wellbeing. However, an analysis of digital health strategies from 10 African countries with young populations suggest that national approaches to digital health are overlooking young people's specific health needs and unique risks in relation to digital technologies and data. To better serve the needs of children and youth in a digital age, future digital health strategies—and the global guidance that many strategies are based upon—should consider the ways in which digital transformations can positively or negatively impact the health and wellbeing of different populations, and the forms of cross-sectoral and multi-stakeholder collaboration required to amplify or mitigate them. Future strategies should be developed through inclusive processes that support young people's right to participate in decision-making that affects their lives.